Biomedical Applications of Silver Nanoparticles (Review) - D. T. Rejepov; A. A. Vodyashkin; A. V. Sergorodceva; Ya. M. Stanishevskiy (Разработка и регистрация лекарственных средств, 2021)
Introduction. Silver nanoparticles have unique physicochemical properties and can be used for the diagnosis and treatment of various kinds of infections, oncological diseases, as well as drug delivery. The review presents an analysis of scientific literature on the use of silver nanoparticles for biomedical purposes.Text. The review discusses the perspectives of the silver nanoparticles use in the treatment of oncological diseases as a carrier of drugs, as well as the direct manifestation of their cytotoxic effect on cancer cells. Also, there is considered the use of silver nanoparticles for imparting or enhancing the antibacterial effects of dressings and dental materials. The mechanism of action of silver nanoparticles against viruses is considered. This research presents the use of composite materials containing silver nanoparticles for biomedical purposes.Conclusion. On the basis of the literature data analysis, carried out by the authors, there are shown possibilities of the nanotechnology achievements for the application in medicine.